Eksplorasi Struktur dan Refleksi Nilai Sosial dalam Cerpen Sekotak Cinta Bersampul Koran - Nabilah Batu Bara; Abdurahman Abdurahman (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
This study aims to explore the structure and social values contained in the short story Sekotak Cinta Bersampul Koran by Seno Gumira Ajidarma with a focus on how this short story describes the social conditions of society and the inner struggle of the main character. Through a literary analysis approach, this study analyzes the story structure, characters, themes, and storytelling techniques used in the short story. The results of the analysis show that this short story reflects the social alienation experienced by individuals in modern life, as well as the inner conflicts that arise due to social and economic injustice. It also highlights the values of love and sacrifice, friendship and solidarity, and social justice and injustice, leading to a critique of materialistic social norms. A clear plot structure, starting from introduction, conflict, climax, to resolution, supports the delivery of the theme, showing the inner struggle of the main character in finding the meaning of life and love in the midst of social limitations. This research is expected to provide deeper insights into the influence of literature in reflecting social issues and enriching readers' understanding of Indonesian literary works, as well as inviting readers to be more critical in assessing literary works as a reflection of existing social reality.